Rift Valley Fever Virus Circulating among Ruminants, Mosquitoes and Humans in the Central African Republic - (:unkn) unknown (My University, 2016)
Background: Rift Valley fever virus (RVFV) causes a viral zoonosis, with discontinuous epizootics and sporadic epidemics, essentially in East Africa. Infection with this virus causes severe illness and abortion in sheep, goats, and cattle as well as other domestic animals. Humans can also be exposed through close contact with infectious tissues or by bites from infected mosquitoes, primarily of the Aedes and Culex genuses. Although the cycle of RVFV infection in savannah regions is well documented, its distribution in forest areas in central Africa has been poorly investigated.Methodology/principal findings: To evaluate current circulation of RVFV among livestock and humans living in the Central African Republic (CAR), blood samples were collected from sheep, cattle, and goats and from people at risk, such as stock breeders and workers in slaughterhouses and livestock markets. The samples were tested for anti-RVFV immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies. We also sequenced the complete genomes of two local strains, one isolated in 1969 from mosquitoes and one isolated in 1985 from humans living in forested areas. The 1271 animals sampled comprised 727 cattle, 325 sheep, and 219 goats at three sites. The overall seroprevalence of anti-RVFV IgM antibodies was 1.9% and that of IgG antibodies was 8.6%. IgM antibodies were found only during the rainy season, but the frequency of IgG antibodies did not differ significantly by season. No evidence of recent RVFV infection was found in 335 people considered at risk; however, 16.7% had evidence of past infection. Comparison of the nucleotide sequences of the strains isolated in the CAR with those isolated in other African countries showed that they belonged to the East/Central African cluster.Conclusion and significance: This study confirms current circulation of RVFV in CAR. Further studies are needed to determine the potential vectors involved and the virus reservoirs.
Keywords: African Research